2022
DOI: 10.1111/iej.13681
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative endodontic procedures for the treatment of necrotic mature teeth: A preliminary randomized clinical trial

Abstract: Aim: This preliminary randomized, prospective, controlled trial aimed to compare the clinical and radiographic outcomes of two regenerative endodontic procedures (REPs), revitalization and a platelet-rich fibrin (PRF)-based technique, in the treatment of mature permanent teeth with necrotic pulps. Methodology:The trial has been reported according to the Preferred Reporting Items for Randomized Trials in Endodontics 2020 guidelines. The study protocol was registered at the clinical trial registry (Clini calTr i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 66 publications
(89 reference statements)
1
6
0
Order By: Relevance
“…Regarding the radiographic healing, preoperative and follow‐up records after 6 and 12 months showed a significant decrease in the periapical lesion size in both groups, these results are in agreement with El‐Kateb et al (2020) and Youssef et al (2022). Alagl et al (2017), Jadhav et al (2012), and Shivashankar et al (2017) showed that PRP revascularization was better than blood clot and PRF concerning periapical healing.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the radiographic healing, preoperative and follow‐up records after 6 and 12 months showed a significant decrease in the periapical lesion size in both groups, these results are in agreement with El‐Kateb et al (2020) and Youssef et al (2022). Alagl et al (2017), Jadhav et al (2012), and Shivashankar et al (2017) showed that PRP revascularization was better than blood clot and PRF concerning periapical healing.…”
Section: Discussionsupporting
confidence: 90%
“…15 Full – text articles were assessed for eligibility. After full article screening, 5 references were excluded with reasons ( 12 - 16 ) ( Table 1 ). Finally, ten randomized controlled clinical trials met the inclusion criteria for qualitative synthesis ( 6 , 17 - 25 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PRF contains autologous high-density fibrin clots that act as a biological scaffold to support cell proliferation and migration; it also allows an increase in the concentration of local growth factors, stimulates regeneration of diseased pulp tissue, and promotes the formation of dentin and periapical bone tissue. Ahmed Youssef et al applied PRF to treat adult permanent anterior teeth with pulpal necrosis, and they showed significant improvement in pulp vitality and significant healing of periapical bone tissue at 6-month and 12-month postoperative follow-ups ( Youssef et al, 2022 ). In addition, Le Fort I osteotomy is most commonly used to correct osseous Class III maxillary deformities, and the critical factor for its success is the long-term stability of the bone block.…”
Section: The Application Of Prf In Dentistrymentioning
confidence: 99%